2015
DOI: 10.1007/s12098-015-1961-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Distress Syndrome: A Rare Complication in Pediatric Diabetic Ketoacidosis

Abstract: Cerebral edema (CE) and non cardiogenic pulmonary edema (acute respiratory distress syndrome, ARDS) are life-threatening complications of diabetic ketoacidosis (DKA). In contrast to CE complicating DKA, which is primarily reported in pediatric patients, ARDS is rarely described in this age group. Here, the authors present a child with DKA who developed both cerebral edema and ARDS during the course of her management. It is feasible that severe acidosis, hypotension, azotemia, hypoalbuminemia and the superimpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The mortality rate from DKA in children is 0.15%-0.30% and the major cause that accounts for 60%-90% of all DKA deaths is cerebral edema ( 8 ). Among other causes of mortality and morbidity, ARDS also presents a predictor of high mortality but this entity is rarely encountered in pediatric population ( 8 , 10 , 11 ). The true mechanism of ARDS during DKA remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality rate from DKA in children is 0.15%-0.30% and the major cause that accounts for 60%-90% of all DKA deaths is cerebral edema ( 8 ). Among other causes of mortality and morbidity, ARDS also presents a predictor of high mortality but this entity is rarely encountered in pediatric population ( 8 , 10 , 11 ). The true mechanism of ARDS during DKA remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It can be speculated that severe acidosis as in our patient with DKA could cause an increase in the permeability of capillary membranes, leading to alteration of the alveolar surfactant metabolism ( 4 ). However, many patients are very acidotic at the onset of DKA but only few of them develop ARDS ( 11 ). This supports the hypothesis of the multifactorial etiology of ARDS as a complication of DKA ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also revealed the independent association of severe respiratory distress followed by hypoxemic respiratory failure with cerebral edema 19 and diabetic ketoacidosis-related cerebral edema. 20 A number of previous studies also showed that severe sepsis and its cascades are associated with cerebral edema. 21 We treated the study children with cerebral edema either with mannitol or 3% NaCl.…”
Section: Discussionmentioning
confidence: 97%
“…However, with an increase in the number of hospitalizations in DKA over the years, up to 27% of cases were found to be from type 2 diabetes [4]. The major clinical difference between these two types of diabetes is a lesser degree of acidosis and absence of hyperkalemia in type 2 diabetes [5].…”
Section: Discussionmentioning
confidence: 99%